Steroid Resistant CD8+CD28null NKT-Like Pro-inflammatory Cytotoxic Cells in Chronic Obstructive Pulmonary Disease - Hodge, Greg; Hodge, Sandra (Frontiers in Immunology, 2016)
Corticosteroid resistance is a major barrier to effective treatment in chronic obstructive pulmonary disease (COPD), and failure to suppress systemic inflammation in these patients may result in increased co-morbidity. Although much of the research to date has focused on the role of macrophages and neutrophils involved in inflammation in the airways in COPD, recent evidence suggests that CD8+ T cells may be central regulators of the inflammatory network in this disease. CD8+ cytotoxic pro-inflammatory T cells have been shown to be increased in the peripheral blood and airways in patients with COPD whereas smokers that have not progressed to COPD only show an increase in the lungs. Although the mechanisms underlying steroid resistance in these lymphocytes is largely unknown, new research has identified a role for cytotoxic pro-inflammatory CD8+ T-cells and CD8+ natural killer T-like (NKT-like) cells. Increased numbers of these cells and their significant loss of the co-stimulatory molecule CD28 has been shown in COPD, consistent with findings in the elderly and in clinical conditions involving chronic activation of the immune system. In COPD, these senescent cells expressed increased levels of the cytotoxic mediators perforin and granzyme b and the pro-inflammatory cytokines IFNγ and TNFα. They also demonstrated increased cytotoxicity towards lung epithelial cells and importantly were resistant to immunosuppression by corticosteroids compared with their CD28+ counterparts. Further research has shown these cells evade the immunosuppressive effects of steroids via multiple mechanisms. This mini review will focus on cytotoxic pro-inflammatory CD8+CD28null NKT-like cells involved in COPD and novel approaches to reverse steroid resistance in these cells.